SAE Technical Paper Series 1999
DOI: 10.4271/1999-01-2238
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Reducing Aerodynamic Drag for Higher Efficiency of Heavy Duty Trucks (Class 7-8)

Abstract: This paper describes research and development for reducing the aerodynamic drag of heavy vehicles by demonstrating new approaches for the numerical simulation and analysis of aerodynamic flow. In addition, greater use of newly developed computational tools holds promise for reducing the number of prototype tests, for cutting manufacturing costs, and for reducing overall time to market.Experimental verification and validation of new computational fluid dynamics methods are also an important part of this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 1 publication
1
6
0
1
Order By: Relevance
“…Both indicate a large area of low pressure acting within 0.5 < z* < 1.1, as well as an isolated region of higher pressure located at a top centreline location (1.3 < z* < 1.35). This topology is well known and agrees with that reported previously (Horrigan et al 2007;Storms et al 2001;Bayraktar et al 2005; (2) McCallen et al 1999;Gutierrez et al 1996) as the result of the recirculating wake structure encompassing a proximate bottom vortex core responsible for the minimum Cp magnitudes identified at z* ≈ 0.7-0.8, and upper recirculating flow impingement, for higher magnitudes adjacent to the top edge [y* ≈ 0, z* ≈ 1.35- (Perry et al 2016;Pavia et al 2017;Castelain et al 2018)]. The former appears subtly more pronounced for the stationary ground case, suggesting a stronger influence.…”
Section: Time-averaged Base Pressure Coefficientssupporting
confidence: 92%
“…Both indicate a large area of low pressure acting within 0.5 < z* < 1.1, as well as an isolated region of higher pressure located at a top centreline location (1.3 < z* < 1.35). This topology is well known and agrees with that reported previously (Horrigan et al 2007;Storms et al 2001;Bayraktar et al 2005; (2) McCallen et al 1999;Gutierrez et al 1996) as the result of the recirculating wake structure encompassing a proximate bottom vortex core responsible for the minimum Cp magnitudes identified at z* ≈ 0.7-0.8, and upper recirculating flow impingement, for higher magnitudes adjacent to the top edge [y* ≈ 0, z* ≈ 1.35- (Perry et al 2016;Pavia et al 2017;Castelain et al 2018)]. The former appears subtly more pronounced for the stationary ground case, suggesting a stronger influence.…”
Section: Time-averaged Base Pressure Coefficientssupporting
confidence: 92%
“…In a typical class 8 tractor/trailer, power required to overcome rolling resistance and accessories increase linearly with vehicle speed, while energy losses due to aerodynamic drag increase with the cube of the speed. At a typical highway speed of 70 mph, aerodynamic drag accounts for approximately 65% of the energy output of the engine (McCallen et al 1999). Due to the large number of tractor/trailers on the US highways, even modest reductions in aerodynamic drag can significantly reduce domestic fuel consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several options for improvement in the fuel economy, such as enhancing the engine performance, 1 decreasing the automobile weight and reducing the aerodynamic drag. 2,3 However, for a medium-size sedan, aerodynamic drag accounts for nearly 20% of the fuel consumption at 100 km/h and, for a heavy commercial vehicle, about 50% of fuel 4 is consumed to overcome the aerodynamic drag. Furthermore, the power consumption of the aerodynamic drag is proportional to the cube of the velocity, and the related studies have revealed that a reduction of 10% in the aerodynamic drag can reduce the fuel consumption by about 7%.…”
Section: Introductionmentioning
confidence: 99%